2003
DOI: 10.1038/nature02156
|View full text |Cite
|
Sign up to set email alerts
|

Visual control of action but not perception requires analytical processing of object shape

Abstract: The visual perception of object shape depends on 'holistic' processing in which a given dimension cannot be perceptually isolated from the other dimensions of the object. The visual control of action (such as grasping an object), however, which is mediated by cortical areas that are largely independent of those mediating conscious perception, must take into account only the most action-relevant dimension of an object without being misled by other non-relevant object features. Here we report the results of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
165
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 25 publications
24
165
4
Order By: Relevance
“…1l; the Square-diamond illusion in Fig. 1m; see Ganel & Goodale, 2003;Ben-Shalom & Ganel, 2012). It then follows that if there is a perceptual style for local processing then reduced susceptibility is more likely to be seen in the former than the latter class of illusions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1l; the Square-diamond illusion in Fig. 1m; see Ganel & Goodale, 2003;Ben-Shalom & Ganel, 2012). It then follows that if there is a perceptual style for local processing then reduced susceptibility is more likely to be seen in the former than the latter class of illusions.…”
Section: Introductionmentioning
confidence: 95%
“…The ordinary rectangle is another example of this type of illusion. The perceptual judgement of its width is always contingent on its length: Longer rectangles are typically perceived narrower than shorter rectangles with the same width (Ganel & Goodale, 2003;Ben-Shalom & Ganel, 2012). Likewise, in the case of both the Shepard's tabletops and Square-diamond illusions, a change in the orientation of the stimulus can change its apparent length and width.…”
Section: Processing Of Within-object Relational Propertiesmentioning
confidence: 99%
“…Recent findings of Ganel and Goodale (2003) show that even for utilizing knowledge about the shape of objects in activities requires analytical, conscious processes whereas perception of the same aspects happens in a holistic way. Thus, here we propose that utilizing the aspect of exact numerosity in action does not occur automatically, but requires intentional processes.…”
Section: Introductionmentioning
confidence: 99%
“…Visual perception depends among other variables, on the form of the object seen. It has been showed that control and visual actions are analyzed in 17 and 18 sensory cortical areas, respectively, when presentation of one object is unidimensional, thus preventing activation of all other areas in the visual cortex 13 ; on the contrary, vision of one object in movement operates 18 and 19 Brodmann areas, respectively. The nasal segment of the visual field of every eye registers the temporal half of the corresponding retina, whereas the temporal region of the visual field registers the nasal half of the retina.…”
mentioning
confidence: 99%